Kinetic Parametrs from TG Analysis of Chloroaquo-bis(3-Methyl-4-Amino-5-Mercapto-1,2,4-Triazole) Copper(I) Complex - Kumar, Ashok; Kumar Sinha, Bijay; Prasad, Girish; Kant, Rewati; Kumar, Sanjeev (Asian Journal of Chemistry, 2010)
In the present work, we describe the kinetic parameters from TG-analysis of a copper(I) complex.